IMPLEMENTATION OF JOB COMMITMENT AND JOB MOTIVATION TOWARD OPTIMIZATION OF JOB SATISFACTION THROUGH EMPLOYEE PERFORMANCE - Maryani, Maryani; Nurhadi, Nurhadi; Adnan, Muhd Adrin Bin (Jurnal Aplikasi Manajemen, 2022)
This research aims to explain the causal relationship between research variables. In this study, the variables observed were work commitment, work motivation, job satisfaction, and employee performance. Related to the research objective, the type of research is explanatory or causality research. The analytical method used is multiple regression analysis. The population of this study involved all employees at PT. Bank Sulselbar in Makassar City amounted to 120 people who later became the research sample. Data analysis or data interpretation was carried out through descriptive statistical analysis. The results showed that work commitment and work motivation directly affected job satisfaction or indirectly affected job satisfaction through employee performance. Employees with high work commitment desire to achieve organizational goals, always think positively about the organization, and give their best efforts for the organization.